PENGEMBANGAN MEDIA PEMBELAJARAN WORD SEARCH PUZZLE TERHADAP KREATIFITAS SISWA PADA MATERI AL-KHABIR SMP IT AL-GHAZALI PALANGKA RAYA - Reza Andri Astuti; Mega Ulpah, Ahmad Maulana (ADISAM PUBLISHER, 2025)
This study aims to evaluate the effectiveness of developing the Word Search Puzzle educational media in enhancing students' creativity regarding the Al- Khabir material at SMP IT Al-Ghazali Palangka Raya. This innovative educational media was developed to address the issues of low student engagement and motivation encountered during the learning process. The research method employed is Research and Development (R&D) with the 4-D development model, which involves distributing questionnaires and conducting interviews to collect data from teachers and students. The results indicate that the use of Word Search Puzzle significantly improves students' understanding and motivation, creating a more enjoyable and interactive learning experience. All students reported ease in understanding the material and an increase in learning enthusiasm. Despite some challenges related to supporting facilities affecting the effectiveness of this media, Word Search Puzzle proves effective in boosting students' creativity. The study recommends exploring other educational media that can accommodate various learning styles and improving supporting facilities at the school to enhance learning effectiveness